The Implementation of Good Local Governance: An Analysis in Former Mining Areas - Hidayat, Novendra; Fatah, Abdul; Fienda, Tiara Elgi; Ansyari, Irvan (Berumpun: International Journal of Social, Politics, and Humanities, 2023)
The main focus of reform in Indonesia is the realization of a civil society that embodies the principles of good governance. The study aims to examine and analyze the phenomenon of good local governance in Sawahlunto’s Municipality. This study employs a qualitative approach with a descriptive case study. The data collection technique is conducted through interviews, documentation, and observation, employing the triangulation of data. The informants were selected via purposive sampling. The conclusion drawn from this study is that, in terms of accountability, it must be published in the LAKIP and LKPJ as a tool of government information systems, and it is recommended that private accountants conduct audits on specific programs or activities. For Transparency, conducting public hearings for every policy decision concerning public interests, publishing every service procedure, establishing a Short Message Service (SMS) Centre, and holding regular meetings between the local government and stakeholders. The involvement of the community in the planning, implementation, and monitoring of development activities is facilitated through various mechanisms such as the Village and Sub-district Development Planning Meeting (Musrenbang Desa dan Kelurahan), the District Development Planning Meeting (Musrenbang Kecamatan), the Forum of Regional Work Units (Forum SKPD), and the City Development Planning Meeting (Musrenbang Kota). These processes aim to stimulate the grassroots economy and establish the City Development Facilitator (Fasbangkot).